Implementasi Nilai-Nilai Kedisiplinan dalam Ibadah Santri di Pondok Pesantren Raudhlatul Ulum Banyugiri - Noer Laili Rohmadhoni Novita Fitri; Nazahah Ulin Nuha; Devy Habibi Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of religious discipline values ​​in character building of students at the Raudlatul Ulum Banyugiri Islamic Boarding School. Religious discipline is understood as the students' obedience, regularity, and awareness in carrying out scheduled religious activities such as congregational prayer, reading the Qur'an, dhikr, and other religious activities. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that the implementation of religious discipline is carried out through habituation, role models, supervision, implementation of rules, and management of a religious Islamic boarding school environment. These values ​​have been proven to have a positive impact on the character building of students, especially in aspects of responsibility, regularity, compliance with rules, and increasing spiritual awareness. In addition, religious discipline also plays a role in shaping students' ability to manage time and build a regular lifestyle. The main supporting factors in this implementation include the role of caregivers and ustaz/ustazah, a clear system of rules, and a religious Islamic boarding school culture, while the obstacles found are related to the varying levels of individual students' awareness. Thus, religious discipline in Islamic boarding schools plays a strategic role in strengthening character education, which is oriented towards developing religious, disciplined, and responsible students.